2017
DOI: 10.1088/1361-6455/aa9955
|View full text |Cite
|
Sign up to set email alerts
|

Electron-correlation study of Y iii-Tc vii ions using a relativistic coupled-cluster theory

Abstract: Abstract. Spectroscopic properties, useful for plasma diagnostics and astrophysics, of a few rubidium-like ions are studied here. We choose one of the simplest, but correlationally challenging series where d− and f − orbitals are present in the core and/or valence shells with 4d 2 D 3/2 as the ground state. We study different correlation characteristics of this series and make precise calculations of electronic structure and rates of electromagnetic transitions. Our calculated lifetimes and transition rates ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…Similarly, we have compared the absorption oscillator strengths of various transitions of Nb V in Table 4, according to which, our results are in good agreement with the results given by Das et.al. (Das et al 2017). A deviation of less than 10% is seen during the comparison of our results with the data published in (Migdalek 2016), except for the 4D 3/2 → 5P 1/2 and 4D 5/2 → 5P 3/2 transitions.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Similarly, we have compared the absorption oscillator strengths of various transitions of Nb V in Table 4, according to which, our results are in good agreement with the results given by Das et.al. (Das et al 2017). A deviation of less than 10% is seen during the comparison of our results with the data published in (Migdalek 2016), except for the 4D 3/2 → 5P 1/2 and 4D 5/2 → 5P 3/2 transitions.…”
Section: Resultssupporting
confidence: 69%
“…In this table, it is seen that the results for the transition probabilities and absorption oscillator strengths agree well with each other within the quoted error limits. We have found that our results are in perfect accord with the previous data published by Migdalek and Baylis (Migdalek & Baylis 1979) and are in fair agreement with the results reported by Migdalek in (Migdalek 2016) and Das et.al (Das et al 2017) except for the 4D 3/2 → 5P 1/2 and 4D 5/2 → 5P 3/2 transitions. However, our results do not support the values obtained by Zilitis in (Zilitis 2007).…”
supporting
confidence: 94%
See 2 more Smart Citations
“…The calculation of dipolar polarizability is based on the sum-over-state [36,37] formalism in which the accurate calculations of E1 matrix elements of 137 Ba + play an important role as the other factors, energy levels of the ion, are extracted from experimental measurements. As stated earlier, we employ correlation exhaustive relativistic coupled-cluster singles, doubles, and partial triple [RCCSD(T)] formalism [42][43][44][45][46][47] to calculate the most dominating E1 matrix elements. Gaussian type orbital (GTO) basis [44,48] with optimized [49] even-tempered exponents [50] is considered to generate precise wavefunctions at the DF (Dirac-Fock) level.…”
Section: Resultsmentioning
confidence: 99%